FAKTOR BI RATE, INFLASI DAN KURS RUPIAH TERHADAP PEMBIAYAAN KREDIT UMKM - Steven stevens; Felicia Celesta celesta; Silvia silvia; Yeni Ariesa ariesa (JEBIM Prima, 2022)
Currently, in developing countries, MSMEs have a big contribution to grow the community's economy, including Indonesia. MSMEs hold an essential position in economic progress. There are still very few researchers who examine the BI Rate, Inflation, and the Rupiah Exchange Rate on MSME credit financing. So, researchers are interested in taking this title. This study is an explanatory research which aims to describe the causal correlation between variables through hypotheses and is carried out through descriptive analysis. The population in this study is all MSMEs in Indonesia that receive credit financing. The data taken is the period 2011-2019. Population data collection techniques are carried out using a time series approach using an annual scale. The result is that the BI Rate, Inflation and the Rupiah Exchange rate partially have no effect and are not significant on MSME credit financing. Meanwhile, the BI Rate, Inflation, and the Rupiah Exchange simultaneously have a significant effect on MSME credit financing.